Persepsi dan Pemaknaan Nilai Kemaslahatan pada Implementasi Program Makan Bergizi Gratis (MBG) dalam Perspektif Ekonomi Islam: Studi pada SD Negeri 030413 Salak Kabupaten Pakpak Bharat - Pajhar Ainnun Berutu; Nurbaiti Nurbaiti; Purnama Ramadani Silalahi (Jurnal Riset Akuntansi, 2026)
This study aims to explore the perceptions and meanings of maslahah (public welfare) values in the implementation of the Free Nutritious Meal Program (MBG) at SD Negeri 030413 Salak, Pakpak Bharat Regency, North Sumatra Province. Pakpak Bharat Regency records a stunting prevalence of 28.9% far exceeding the national average of 19.8% while most beneficiary families are low-income and lack adequate access to nutritious food. This research employs a qualitative approach with a phenomenological design through semi-structured in-depth interviews, participatory observation, and documentation involving nine informants. Data analysis was conducted using the Miles and Huberman interactive model with interpretation based on the maqāṣid al-sharīʿah framework. The findings reveal five integrated dimensions of maslahah: fulfillment of ḥifẓ al-nafs through improvements in students’ physical health; strengthening of ḥifẓ al-ʿaql through increased concentration and learning readiness; preservation of ḥifẓ al-nasl through early intervention against stunting; realization of ḥifẓ al-dīn through religious practices accompanying the program; and protection of ḥifẓ al-māl through reduced household expenditure. Overall, the MBG Program functions not only as a nutritional intervention but also as a public policy aligned with maqāṣid al-sharīʿah, contributing to the multidimensional achievement of falah.